Determination of Parameters of Roller of Wave Transmission with Intermediate Rolling Bodies with Hollow Shaft for Geokhod - Timofeev V. Yu. Vadim Yurievich (Material Science, Machining Technologies and Equipments in Mechanical Engineering, 2014)
Title screen